Dual-specificity protein phosphatase 6 (DUSP6) overexpression reduces amyloid load and improves memory deficits in male 5xFAD mice - Pan, Allen L.; Audrain, Mickael; Sakakibara, Emmy; Joshi, Rajeev; Zhu, Xiaodong; Wang, Qian; Wang, Minghui; Beckmann, Noam D.; Schadt, Eric E.; Gandy, Sam; Zhang, Bin; Ehrlich, Michelle E.; et al. (Frontiers in Aging Neuroscience, 2024)
Dual specificity protein phosphatase 6 (DUSP6) was recently identified as a key hub gene in a causal VGF gene network that regulates late-onset Alzheimer’s disease (AD). Importantly, decreased DUSP6 levels are correlated with an increased clinical dementia rating (CDR) in human subjects, and DUSP6 levels are additionally decreased in the 5xFAD amyloidopathy mouse model. To investigate the role of DUSP6 in AD, we stereotactically injected AAV5-DUSP6 or AAV5-GFP (control) into the dorsal hippocampus (dHc) of both female and male 5xFAD or wild type mice, to induce overexpression of DUSP6 or GFP. Barnes maze testing indicated that DUSP6 overexpression in the dHc of 5xFAD mice improved memory deficits and was associated with reduced amyloid plaque load, Aß1-40 and Aß1-42 levels, and amyloid precursor protein processing enzyme BACE1, in male but not in female mice. Microglial activation, which was increased in 5xFAD mice, was significantly reduced by dHc DUSP6 overexpression in both males and females, as was the number of ‘microglial clusters’, which correlated with reduced amyloid plaque size. Transcriptomic profiling of female 5xFAD hippocampus revealed upregulation of inflammatory and extracellular signal-regulated kinase pathways, while dHc DUSP6 overexpression in female 5xFAD mice downregulated a subset of genes in these pathways. Gene ontology analysis of DEGs (p < 0.05) identified a greater number of synaptic pathways that were regulated by DUSP6 overexpression in male compared to female 5xFAD. In summary, DUSP6 overexpression in dHc reduced amyloid deposition and memory deficits in male but not female 5xFAD mice, whereas reduced neuroinflammation and microglial activation were observed in both males and females, suggesting that DUSP6-induced reduction of microglial activation did not contribute to sex-dependent improvement in memory deficits. The sex-dependent regulation of synaptic pathways by DUSP6 overexpression, however, correlated with the improvement of spatial memory deficits in male but not female 5xFAD.